Analysis of the inhibitory effects of chloropicrin fumigation on nitrification in various soil types. (May 2017) - Yan, Dongdong; Wang, Qiuxia; Li, Yuan; Ouyang, Canbin; Guo, Meixia; Cao, Aocheng
Abstract: Chloropicrin retards the conversion of ammonia to nitrite during the nitrification process in soil. In our study, the dynamic effect of chloropicrin fumigation on soil nitrification was evaluated in five different soil types to identify relationships between soil properties and the effect of fumigation on nitrification. Chloropicrin significantly inhibited nitrification in all soils; however, the recovery of nitrification varied greatly between the soils. Following chloropicrin fumigation, nitrification recovered to the control level in all soils, except in the acidic Guangxi soil. Nitrification recovered faster in fumigated sandy loam Beijing soil than in the other four fumigated soils. Soil texture and pH were two important factors that influenced chloropicrin's inhibitory effect on nitrification. An S-shaped function was fitted to soil NO3 − -N content to assess the nitrification recovery tendency in different soils. The time taken to reach maximum nitrification ( t max ) ranged from 2.4 to 3.0 weeks in all unfumigated soils. Results demonstrated that t max was greater in all fumigated soils than in untreated soils. Correlation calculations showed that t max was strongly correlated to soil texture. The correlation analysis results indicated that the recovery rate of nitrification after chloropicrin fumigation is much faster in sandy loam soil than silty loam soil. Highlights: Chloropicrin caused inhibitory effects on nitrification in different soil types. Nitrification recovered faster in sandy loam soils after chloropicrin fumigation. Soil texture and pH were two important factors influencing the inhibitory effect.